(untitled) (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2022)
This paper explores the field of digital social education through a survey on the training and digital competencies of social educators. A total of 145 social educators in Spain participated in the survey through a questionnaire of our own elaboration. An Exploratory Factor Analysis was performed on the variables on digital competencies to assess their validity, together with Cronbach’s Alpha coefficient for reliability. Descriptive statistics are used to know their training and digital competences. The results are oriented to the development of a digital social education program to provide critical digital literacy.